QUALITY OF FINANCIAL CONGLOMERATES’ PERFORMANCE IN EMERGING ECONOMY: THE INDUSTRIAL ORGANIZATION THEORY PERSPECTIVE - Adawiyah, Wiwiek Rabiatul; Pramuka, Bambang Agus (Jurnal Keuangan dan Perbankan, 2017)
Financial conglomerates are financial institutions that provide all forms of financial services on the top of ordinary banking service. The quality of financial conglomerates’ performance depends on a number of factors namely ownership structure, internal capital market, and resources sharing. Research on the performance of financial conglomerates is still lacking in Indonesia.  This study, therefore, is among the first attempt to assess the influence of ownership structure, internal capital market and resources sharing on the performance financial conglomerate firms in Indonesia, from the industrial-organizational theory perspectives. The methodology employed is the ex-post facto research design, using secondary data. The population of the study is all the conglomerate's firms listed on the Indonesian Stock Exchange between 2010 until 2015 persistently. The study used regression as a tool of analysis. Findings supported three out of the five hypotheses proposed.  Efficient subsidy and managerial ownership had no significant influence on firms’ performance. Efficient transfer segment had a positive influence on firms’ performance.  Similarly, the result supported the proposition that intangible and tangible resources had a positive effect on firms’ performance.DOI: https://doi.org/10.26905/jkdp.v21i2.649